The literary criticism of T.S. Eliot : new essays - Newton-De Molina, David (London : Athlone Press, 1977)
Includes comments on his criticism of other literary forms.
Includes index.
Keywords: Eliot, T. S. -- 1888-1965.; Poetry in English -- Criticism -- Eliot, T -- S. - Critical studies